Analisis Minat Anggota Untuk Melakukan Pembiayaan Secara Syariah di Koperasi Sulit Air Sepakat (SAS) - Hari Setia Putra; Ullya Vidriza (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2022)
The purpose of this study is to find out the factors that become members' interest in sharia financing at Koperasi Sulit Air Sepakat (SAS) Padang City. In understanding the phenomena that occur with the research subject, it is done by giving a questionnaire containing questions as a research instrument and a total of 68 people who are respondents in this study. From this study it was found that the regulatory policies applied, halal principles, profit sharing systems and trustworthiness had a significant effect in increasing members' interest in sharia financing at SAS Padang City, but the lack of information and services and promotions carried out were not considered optimal so that this made the interest of members reduced to carry out financing in the cooperative. What can be recommended in this study is that the Koperasi SAS Padang City should be able to provide regular socialization so that members get more information regarding the administrative process, services and products offered in financing using the concept of sharia. Because this is really needed by members in the hope that member interest in sharia financing will increase